A Study of Nodular Skin Lesions with Special Reference to the Ethnic Population of Northeast India in a Tertiary Care Hospital - Paul, Sanchita; Kalita, Abhijit; Kaushik, Neha (Annals of Pathology and Laboratory Medicine, 2022)
Background: Nodular skin lesions vary significantly in size and colour/pigmentation. Most of these clinically resemble soft tissue lesions. Histopathology plays key role in categorizing the lesions based on which course of treatment is planned. The present study aims to find out incidence and variation of skin nodules and correlate the clinico-pathological details with special reference to ethnic population of Northeast India. Methods: The study is a retrospective and descriptive study conducted for a period of 2 years at a tertiary care centre. The clinical and demographic details were retrieved and H&E slides are studied for histomorphology. Result: A total of 50 cases were studied out of which five cases were diagnosed as malignant tumours and 45 cases were diagnosed as benign tumours. Seventeen cases (34%) of tumours with follicular differentiation, eight cases (16%) of melanocytic tumours, nine cases (18%) of vascular and neural tumours, thirteen cases (26%) of tumours with apocrine and eccrine differentiation, two cases (4%) of epidermal tumors and one case (2%) of tumour with sebaceous differentiation were included under the present study. Tumors with follicular differentiation, the most commonly encountered tumor in the present study, were seen in the fourth to sixth decades of life and seen more commonly among women. A total of 18 (36%) cases belonged to ethnic tribal communities of North-east India, out of which seven were tumors of follicular differentiation, five were melanocytic tumours and six were tumors of eccrine differentiation. Conclusion: H&E-stained sections stand as the most important tool for diagnosing and differentiating skin nodular lesions. A significant percentage (36%) of the lesions in the present study have been seen in the ethnic population of the Northeast region of India.